FEAR OF MISSING OUT (FOMO) TERHADAP PERILAKU SELF INJURY PADA REMAJA PEREMPUAN - Oetari Nur Rahmadini; Hanifa A’ziz A’qila; Sipa Ainun Habibah; Indah Salsabila Pratiwi (Cahaya Ilmu Bangsa Institute, 2025)
Self-injury is self-injurious behavior without the intention of ending one's life as a way to cope with emotional distress. Adolescent girls often commit non-suicidal self-injury (NSSI) due to peer pressure. The purpose of this study is to understand how fear of missing out (FoMO) can influence adolescent girls who are in junior high school to commit NSSI. This study used a qualitative approach with data collection techniques through semi-structured interviews. The subjects in this study consisted of 4 adolescent girls who had a history of NSSI in the last 6 months. The results showed that the adolescents knew and committed self-harm or NSSI from their peers due to the sense of FoMO as well as the emotional and social pressures they faced, barcode (wrist cutting), hair pulling, self-hitting and pinching are forms of NSSI committed by the 4 adolescent girls.